2023
DOI: 10.26833/ijeg.987605
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between random forest and support vector machine algorithms for LULC classification

Abstract: Nowadays, machine learning (ML) algorithms have been widely chosen for classifying satellite images for mapping Earth's surface. Support Vector Machine (SVM) and Random Forest (RF) stand out among these algorithms with their accurate results in the literature. The aim of this study is to analyze the performances of these algorithms on land use and land cover (LULC) classification, especially wetlands which have significant ecological functions. For this purpose, Sentinel-2 satellite image, which is freely prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The accuracy assessment revealed the excellence of the classification map ( AVCI et al 2021 ). The accuracy assessment of the machine learning algorithm was performed after the classification of LULC to evaluate the performance of the models.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…The accuracy assessment revealed the excellence of the classification map ( AVCI et al 2021 ). The accuracy assessment of the machine learning algorithm was performed after the classification of LULC to evaluate the performance of the models.…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…7,8,9 However RF and SVM algorithms were considered and suggested to be robust algorithms for image classification producing relatively high and consistent classification and regression accuracies. 10,11 RF, first proposed by Leo Breiman in 2001, is an ensemble learning method which utilizes a combination of multiple decision trees to create a stable classification and regression model. 18 This algorithm implements classification by creating multiple decision trees during the training process and combines them through a voting process producing a final prediction model.…”
Section: Related Studiesmentioning
confidence: 99%
“…18,19 But despite the different implementation of classification or regression process, these two algorithms have become commonly used due to their flexibility making them capable of handling large and high-dimensional data with non-linear relationships. 18,19 Between the two algorithms, studies such as Sheykhmousa et 10,12,13,14,15,16,17 With regards modeling of benthic habitats using remote sensing data, supervised image classification using machine learning algorithms like SVM and RF has been common algorithms. 17,21 However, while one algorithm can outperform the other such as in the study of Wicaksono et al in 2019, the use of the dataset and other derivatives have been found to be strongly contributing to the algorithms capability to accurately classify benthic features from the image.…”
Section: Related Studiesmentioning
confidence: 99%
“…For Sentinel-2 the overall accuracy of RF, SVM, DT and CART are 94.8%, 91.79%, 90.84% and 89.30% respectively. In general, RF model gives best performance as it is more reliable and less impacted by its feature [27]. During the process of producing predictions, the final outcome is chosen by averaging the various decision trees that made up the ensemble of decision trees.…”
Section: Land Use Land Cover Classificationmentioning
confidence: 99%